2018
DOI: 10.1002/chem.201705466
|View full text |Cite
|
Sign up to set email alerts
|

A P2‐Type Layered Superionic Conductor Ga‐Doped Na2Zn2TeO6 for All‐Solid‐State Sodium‐Ion Batteries

Abstract: Here, a P2-type layered Na Zn TeO (NZTO) is reported with a high Na ion conductivity ≈0.6×10 S cm at room temperature (RT), which is comparable to the currently best Na Zr Si P O NASICON structure. As small amounts of Ga substitutes for Zn , more Na vacancies are introduced in the interlayer gaps, which greatly reduces strong Na -Na coulomb interactions. Ga-substituted NZTO exhibits a superionic conductivity of ≈1.1×10 S cm at RT, and excellent phase and electrochemical stability. All solid-state batteries hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 32 publications
9
86
0
Order By: Relevance
“…26,27 In the case of the P2-type Na 2 M 2 TeO 6 tellurates oxides materials, the original work reported conductivities of 10 À6 S cm À1 which have been now optimized to reach the mS cm À1 range. 5,12 It is reasonable to expect therefore that similar improvements are possible for the Na 1.5 La 1.5 TeO 6 double perovskite presented here through, for example, aliovalent doping or morphological control.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…26,27 In the case of the P2-type Na 2 M 2 TeO 6 tellurates oxides materials, the original work reported conductivities of 10 À6 S cm À1 which have been now optimized to reach the mS cm À1 range. 5,12 It is reasonable to expect therefore that similar improvements are possible for the Na 1.5 La 1.5 TeO 6 double perovskite presented here through, for example, aliovalent doping or morphological control.…”
supporting
confidence: 58%
“…40 The m + SR measurements indicate that the activation energy required for local Na + diffusion is 0.163(9) eV. This low activation energy is similar to related oxide materials, such as the Ga-doped Na 2 Zn 2 TeO 6 with an activation energy of 0.12 eV as observed from NMR measurements, 12 or b 0 -alumina single crystals with activations energies in the 0.12-0.16 eV range. 41 The higher activation energy values obtained from the macroscopic EIS measurements which probes long range Na + conduction through multiple intra-grain crystalline sites and grain boundaries, compared to microscopic m + SR measurements which are more sensitive to individual Na + hops within the crystalline grain, could have its origin in the contribution to the resistance from grain boundaries to ionic conduction which is virtually invisible to m + SR. Lower conductivity values and higher energy barriers to diffusion could also result from the presence of La 3+ ions in the A-sites, which could hinder longrange Na + conductivity.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…However, K + has a vastly larger ionic radius with a correspondingly larger inter-layer distance and hence forms weaker inter-layer bonds. Generally, A + cations with larger ionic radii such as K + and Na + form weaker inter-layer bonds in the aforementioned compositions resulting in layered oxides with prismatic or octahedral coordination of alkali metal and oxygen (technically referred to as P-type or O-type layered structures, respectively) 1, [3][4][5][6][7][8][9][10][11][12][13][14][15][16]19,20,27,[34][35][36] . The weaker inter-layer bonds in prismatic layered (P-type) structures create more open voids within the transition metal layers allowing for facile two-dimensional diffusion of alkali atoms within the slabs 41 .…”
Section: An Idealised Approach Of Geometry and Topology To The Diffusmentioning
confidence: 99%
“…For ASSBs interface, SEM technique is usually used for observation of morphology of interface between grain of SEs in ASSBs, examining the morphology and determining element composition (combine with EDX) of interface on SEs or electrode. [ 109 ] For example, Li et al [ 110 ] used SEM to observe the particles of Na 2‐ x Zn 2‐ x Ga x TeO 6 ( x = 0, 0.05, 0.1, 0.15) and found that the morphology and density are not influenced by Ga doping; Luo et al [ 111 ] used SEM and EDX to prove the existence of Ge layer on Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 ; Fu et al [ 112 ] used SEM and EDX to characterize morphology of the interface between Li 7 La 2.75 Ca 0.25 Zr 1.75 Nb 0.25 O 12 and metallic Li anode.…”
Section: Characterization Techniques For Interface In All‐solid‐statementioning
confidence: 99%